"Not Nearly as Bad": Social Comparisons and the Debt Experience. (September 2022) - Bryer, Ellen
Despite the growing awareness of the role that families play in the experience of student borrowing, debt is still understood as a private experience. As student debt becomes more widespread, individuals are increasingly likely to know others with student loans, yet questions remain about how others—friends, acquaintances, and colleagues—may shape the way student borrowers make sense of their debt. This study draws on interviews with recent master's degree recipients to examine how young adults understand their educational debt in relation to others. The author finds that borrowers are enmeshed in "debt dense" social networks that both normalize debt and facilitate evaluative social comparisons against others that accentuate borrowers' own efforts and responsibility. These findings demonstrate a role for occupational and educational social networks in shaping borrowers' experience of indebtedness but also suggest limits to framing student debt as a collective problem.